Spring 1995, Peter Petersen & Mary Lou Petersen - Petersen, Mary Louet al; Petersen, Peter C.et al (1995)
An annotated list of birds sighted by Peter Petersen and Mary Lou Petersen with others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Epson - sheet feed/flatbed